Interpersonal therapy for depressed adolescents (The Guilfod Press, 2004)
Fully revised and expanded, the second edition of this popular treatment manual incorporates a decade's worth of scientific and practical advances. Provided are step-by-step guidelines for conducting the authors' evidence-based brief intervention, together with up-to-date information on conceptual and empirical underpinnings. Readers learn how to educate adolescents and their families about depression, work with associated relationship difficulties, and help clients manage their symptoms while developing more effective communication and interpersonal problem-solving skills. Invaluable advice is also given on handling the many challenges and crises that may arise in work with teens. Including many additional clinical vignettes and more detailed instructions throughout, the second edition features two new chapters elucidating specific therapeutic techniques and presenting an extended case example.